GENDER RELATIONS, GLOBALIZATION AND GENDER EMPOWERMENT: THE IMPLEMENTATION OF INDONESIA DIGITAL ENERGY OF ASIA - Enggarratri, Ihsanira Dhevina (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Globalization that is marked by the rapid development of information and communication technology (ICT); is believed to have a great impact on gender relations due to the opportunities provided for both genders to be equally empowered. This research attempts to address the implementation of Indonesia Digital Energy of Asia policy through Gerakan Nasional 1000 Startups Digital practices that aim to promote the participation of the Indonesian community in the global business of the digital industries. This research will discuss the extent of Indonesia Digital Energy of Asia that supports the idea of gender empowerment. This policy implementation has assessed in the context of the process, output, outcomes, and causal connection. Using a qualitative approach, this study discovered the implementation that the policy has been well implemented. This study also discusses the gender empowerment process and socio-economic empowerment. The analytical empowerment framework was also applied to analyze the degrees of gender empowerment. Furthermore, this study reveals that the Indonesia Digital Energy of Asia policy has greatly supported gender empowerment efforts that are also influenced by gender relations among participants of Gerakan Nasional 1000 Startup Digital.